A systematic review of the relationship between muscle oxygen dynamics and energy rich phosphates. Can NIRS help? - Kevin Maliszewski; Andri Feldmann; Kevin K. McCully; Ross Julian (BMC Sports Science, Medicine and Rehabilitation, 2024)
Abstract Background Phosphocreatine dynamics provide the gold standard evaluation of in-vivo mitochondrial function and is tightly coupled with oxygen availability. Low mitochondrial oxidative capacity has been associated with health issues and low exercise performance. Methods To evaluate the relationship between near-infrared spectroscopy-based muscle oxygen dynamics and magnetic resonance spectroscopy-based energy-rich phosphates, a systematic review of the literature related to muscle oxygen dynamics and energy-rich phosphates was conducted. PRISMA guidelines were followed to perform a comprehensive and systematic search of four databases on 02-11-2021 (PubMed, MEDLINE, Scopus and Web of Science). Beforehand pre-registration with the Open Science Framework was performed. Studies had to include healthy humans aged 18–55, measures related to NIRS-based muscle oxygen measures in combination with energy-rich phosphates. Exclusion criteria were clinical populations, laboratory animals, acutely injured subjects, data that only assessed oxygen dynamics or energy-rich phosphates, or grey literature. The Effective Public Health Practice Project Quality Assessment Tool was used to assess methodological quality, and data extraction was presented in a table. Results Out of 1483 records, 28 were eligible. All included studies were rated moderate. The studies suggest muscle oxygen dynamics could indicate energy-rich phosphates under appropriate protocol settings. Conclusion Arterial occlusion and exercise intensity might be important factors to control if NIRS application should be used to examine energetics. However, more research needs to be conducted without arterial occlusion and with high-intensity exercises to support the applicability of NIRS and provide an agreement level in the concurrent course of muscle oxygen kinetics and muscle energetics. Trial registration https://osf.io/py32n/ . Key points 1. NIRS derived measures of muscle oxygenation agree with gold-standard measures of high energy phosphates when assessed in an appropriate protocol setting. 2. At rest when applying the AO protocol, in the absence of muscle activity, an initial disjunction between the NIRS signal and high energy phosphates can been seen, suggesting a cascading relationship. 3. During exercise and recovery a disruption of oxygen delivery is required to provide the appropriate setting for evaluation through either an AO protocol or high intensity contractions.